A transnacionalidade, as migrações transnacionais e os direitos dos trabalhadores migrantes. (2019)
The main objective of this article is to analyze transnationality, transnational migration and the rights of migrant workers. The work is divided into three parts: the first part deals with transnationality and transnational law; the second part deals with transnational migration and its main characteristics; and the third part aims at identifying the rights of migrant workers and the existence of social dumping in Brazilian companies as an offensive practice for the dignity and rights of these workers. The inductive method was implemented using reference and category techniques, operational concepts and bibliographic research. Based on the cases analyzed, it was concluded that the vulnerability condition increases considerably when the worker is also a migrant. Therefore, the practice of social dumping by any company must be strongly fought to avoid any misuse or illegal use of migrant labor since transnational relations and events should not serve as a regression in the application of the rights but be the opposite.